Effect of emotion regulation training on depression, anxiety, and stress among mothers of children with mental disorders - Hossein Jenaabadi (Gonabad University of Medical Sciences, 2017)
Not only mental disorders do affect patients' efficiency, but also they have adverse impacts on families of suffered patients through disrupting their performance. This study aimed to compare the effect of emotion regulation training based on Gross process model and Linehan's dialectical behavior therapy in depression, anxiety, and stress among mothers of children with mental disorders. This was a quasi-experimental study designed as pretest-posttest with a control group. 27 mothers of children with depression and anxiety disorders who admitted to the rehabilitation centers and clinics was selected. They were allocated to three groups including the emotion regulation training based on the Gross's model, the Linehan's dialectical behavior therapy, and the control group. The experimental groups were trained during 8 sessions of 120-150 min. However, the control group received no such interventions. Using the lovibond and lovibond depression, anxiety, and stress scale. The results indicated that there were no significant differences between the mothers placed in the experimental groups; however, compared to the control group, significant decreases in the measured variables were observed in the experimental groups). The emotion regulation training program can be considered as a part of intervention programs conducted at counseling centers and public hospitals for mothers of children with special needs in order to promote mental health and decrease the emotional pain and suffering in the involved family members.